A brief insight into the insect pest of sunflower (Helianthus annuus L.): A BRIEF INSIGHT INTO THE INSECT PEST OF SUNFLOWER - RAIZA NAZRIN; ARCHANA ANOKHE; P DURAIMURUGAN (Journal of Oilseeds Research, 2022)
The sunflower (Helianthus annuus L.) crop has the capacity to quickly adapt to numerous agroecological niches and cropping systems in the Indian subcontinent due to its wide range of adaptation. The major barrier in sunflower production is insect pest damage. It causes damages up to 35-40% damages. The sunflower environment is home to a wide variety of both useful and harmful insect species. Though more than fifty insect species have been reported on sunflower, cutworms (Agrotis spp.), leaf hoppers (Amrasca biguttula biguttula), plant hopper (Empoasca spp.), thrips (Thrips palmi), whitefly (Bemisia tabaci), defoliators (Spilosoma obliqua, Spodoptera litura, and Plusia orichalcea), capitulum borer (Helicoverpa armigera) are major pests of economic concern. With over 180 host plants, including significant crops, Helicoverpa armigera is one of the most devastating and polyphagous insect pests of sunflower.